CO2 hydrogenation to methanol and hydrocarbons over bifunctional Zn-doped ZrO2/zeolite catalysts. Issue 4 (18th January 2021) - Ticali, Pierfrancesco; Salusso, Davide; Ahmad, Rafia; Ahoba-Sam, Christian; Ramirez, Adrian; Shterk, Genrikh; Lomachenko, Kirill A.; Borfecchia, Elisa; Morandi, Sara; Cavallo, Luigi; Gascon, Jorge; Bordiga, Silvia; et al.
Abstract : The tandem process of carbon dioxide hydrogenation to methanol and its conversion to hydrocarbons over mixed metal/metal oxide-zeotype catalysts is a promising path to CO2 valorization. Abstract : The tandem process of carbon dioxide hydrogenation to methanol and its conversion to hydrocarbons over mixed metal/metal oxide-zeotype catalysts is a promising path to CO2 valorization. Herein, we report three Zn-doped ZrO2 catalysts prepared by co-precipitation of Zn- and Zr-containing salts to obtain three different loadings of Zn (5, 15 and 30 wt%). In the context of bifunctional catalysts, we combined ZrZnO X with two of the most performing zeolite/zeotype catalysts for the methanol-to-hydrocarbons (MTH) reaction: H-ZSM-5 and H-SAPO-34. Catalytic testing at 250–350 °C and 20–40 bar revealed that H-ZSM-5 is more stable and more capable of converting methanol at low temperature, whereas H-SAPO-34 shows the highest C3 selectivity. The best performance was observed for the ZrZnO X sample with 30% Zn, combined with ZSM-5 at 350 °C, 30 bar and H2 /CO2 /N2 = 6/2/1. Under these conditions, the equilibrium methanol yield was observed after 0.4 s g −1 ml −1 over ZrZnO X alone. Mixing with ZSM-5 in a 1 : 1 weight ratio, methanol was rapidly converted to hydrocarbons, with an optimum C3 productivity of 1.5 mol kg −1 h −1 at 24 000 ml h −1 g −1 . An extensive surficial, textural and structural characterization of ZrZnO X alone was carried out by FT-IR spectroscopy, N2 adsorption/desorption at liquid nitrogen temperature, PXRD and XAS. Formation of a ZrZnO X tetragonal solid solution was confirmed for all the samples (PXRD, XAS). The amount of Zr 4+ sites at the surface was found to decrease, while the number of oxygen vacancies increased after H2 treatment at 400 °C, coherent with an increase of Zn loading (FT-IR). DFT modelling pointed out that once a stoichiometric oxygen vacancy is induced by the presence of Zn, the formation of extra oxygen vacancies during activation is thermodynamically favored. Moreover, i) the oxygen vacancies were found to play an active role in CO2 hydrogenation, in accordance with experimental data, and ii) methanol is most likely formed via the formate pathway, and is energetically favored compared to CO formation, in agreement with the high methanol selectivity observed experimentally at low CO2 conversion. Importantly, operando -XAS, XPS, TEM and PXRD studies of the as-prepared, pretreated and tested catalysts showed that the structure and composition of the catalyst is not affected by the reaction. Indeed, a final catalytic test carried out on the regenerated ZrZnO X /H-ZSM-5 catalyst showed that the initial performances were completely restored and no Zn exchange in the zeolite was observed neither before nor after testing.